Forensic Accounting and Fraud Detection: A Systematic Literature Review and Prevention Methods - Dipti Singh; Manjeet Kumar; Parul Garg; Manuha Nagpal; Sunil Kumar Yadav (Indian Journal of Forensic Medicine and Pathology, 2025)
The aim of this study is to identify the role of forensic- accounting-that plays a vital role in, detecting & preventing fraud as well as to address pertinent investigation concerns. “Accounting principles, theories and procedures are applied in forensic accounting to analyse the problems in a legal way and contain every field of accounting.-.”Forensic> accounting< is a specialised area of accounting which includes auditing and investigative analytical skills.[4] Forensic accounting is required because corporate crises are happening more frequently all over the world. Financial fraud poses the greatest threat to the economy, making forensic accountants and traditional auditors crucial. Therefore, this study looks into fraud detection methods and ways to prevent it. In order to recognise and identify the current literature on forensic accounting and its preventative techniques, this study used the Preferred Reporting Method for Systematic Literature Reviews (SLR). It has been determined from this research that very few studies have analysed forensic accounting employing SLR techniques. This study also completes an integrated analysis with a concentration on three distinct areas: forensic accounting frauddetection, fraud prevention, methods & policy implementation.